A study on causes and recurrence of the Mid-Mediterranean Jet from 2003 to 2015 using satellite thermal and altimetry data and CTD casts. Issue 1 (2nd January 2021) - Ciappa, Achille
ABSTRACT: The existence of the Mid-Mediterranean Jet (MMJ) as part of the pathway of the Atlantic Water (AW) in Eastern Mediterranean is still debated and the reasons for its formation are unknown. The MMJ was investigated over the 2000–2015 summers using thermal and altimetry satellite data and 'in situ' casts. In the Levantine basin, the AW flowing along the Libyan-Egyptian coast splits into an along-shore and an offshore branch, the latter following the northern border of the warm anti-cyclones located near the African coast (Libyan-Egyptian Eddies, LEEs). The MMJ is triggered when a surface cold water mass formed south-east of Crete, in part outflowing the Aegean Sea and in part generated within the Rhodes Gyre, moves southward and intrudes the middle Levantine basin. The surface cold water overlays the AW flowing along the northern periphery of LEEs that sinks dozens of metres below increasing its budget of anti-cyclonic vorticity and causing the formation of the jet. Satellite data show that the MMJ formed every summer from 2003 to 2015, sometimes for limited periods of time and at different latitudes, with the exception of summers 2005–2006, probably due to the weakness of the African anti-cyclones that in those years did not advect AW offshore.